Serološke in funkcijske preiskave pri diagnosticiranju trombocitopenije, povzročene s heparinom (HIT) - Maličev, Elvira (Zdravniški vestnik, 2012)
Heparin-induced thrombocytopenia (HIT) is an immune-mediated reaction occurring in 3 - 5 % of patients receiving heparin therapy for more than 5 days, which can lead to arterial and venous thrombosis. It is caused by IgG antibodies directed against platelet factor 4/heparin complexes, leading to platelet activation, platelet depletion and thrombocytopenia. Prolonged therapy with heparin can result in serious adverse consequences, so prompt diagnosis is of key importance for the introduction of supplemental therapy. The diagnosis of HIT is based on clinical criteria as well as on serological and functional laboratory assays. Serological assays that identify the presence of platelet factor 4/heparin antibodies in the serum are not sufficient for confirmation of diagnosis because all detected antibodies are not capable of causing thrombocytopenia and thrombosis. Since the usual enzyme-immune assays detect the presence of antibodies but not also their pathogeneity it is recommended to confirm HIT with a functional assay that confirms the capacity of HIT antibodies to activate or aggregate platelets. One of newer functional methods is the flow cytometric analysis of P-selectin (CD62P) expression on the standard platelets after exposure to the patientćs serum. In our experience, this test, in parallele with standard serological tests, proved its reliability for the confirmation of clinical HIT diagnosis.
Keywords: Adverse Effects; Antibodies; Chemically Induced; Diagnosis; diagnostika; Heparin; Igg; Platelet Activation; Platelet Aggregation; Platelet Factor 4; Protitelesa; P-Selectin; P-selektin; Thrombocytopenia; Trombocit, aktivacija; Trombociti, agregacija; Trombocitni faktor 4; Trombocitopenija